Towards a Metropolitan City Centre for Brussels - Berger, Mathieu (Brussels Studies Institute Series, 2020)
Between 2015 and 2020, the city centre of Brussels witnessed the creation of its first major pedestrian zone, one of the largest urban projects in recent decades. Has the Brussels city centre finally done away with the car hegemony? Can the city centre be extended to become the centre of the Brussels metropolis where everyone can find his or her own place? This book presents scientific background to the issue and brings together in words and images the research carried out over the past four years by the Brussels Centre Observatory.